Pre-Trial Legalefforts Due to the Establish Ment of the Suspective Criminalactions of the Corruption Eradiction Commission (KPK) - Syaepul Rohman; Aziz Budianto (Publikasiku, 2023)
Violating the provisions of Law Number 31 of 1999 concerning Eradication of Criminal Acts of Corruption as amended by Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning Eradication of Criminal Acts of Corruption, the alleged perpetrators must be carried out due process. law enforcement to prove that the party can be proven guilty or innocent, which is carried out based on formal legal provisions, namely Law Number 8 of 1981 concerning the Criminal Procedure Code or abbreviated as KUHAP. One of the legal efforts to ratify or not determine the suspect is through pretrial legal efforts. The research problems are; 1. What is the legal action of the KPK investigators based on the Criminal Procedure Code in determining the suspect as the perpetrator of a corruption crime? The research method is carried out through the Approach Method, namely; normative juridical research. The results of this study, that; The competence of the KPK's authority, according to Law Number 30 of 2002 concerning the Corruption Eradication Commission, is substantively responsible for operations in terms of carrying out legal actions for investigating and prosecuting perpetrators of criminal acts of corruption, based on Article 6 point c, Article 7 point a, Article 8 paragraph (2), Article 10, Article 11, Article 12 and Article 62 related to the provisions of the procedural law of actions and legal remedies. Upon the determination of the suspect as the perpetrator of a criminal act of corruption, the person concerned shall carry out Pretrial Legal Efforts. The decision of the pre-trial lawsuit was granted and the determination of the suspect was declared legally flawed. For this reason, it is recommended that in order to avoid the possibility of arbitrariness in legal action by KPK investigators in conducting investigations that end in the determination of suspects, the KPK Supervisory Board should be active in conducting supervision and providing sanctions against investigators if the suspect is proven to be illegal and legally flawed.